1992
DOI: 10.1002/tera.1420460606
|View full text |Cite
|
Sign up to set email alerts
|

The perception of teratogenic risk of cocaine

Abstract: While there has been a substantial increase in recreational use of cocaine by young adults, conclusive evidence for cocaine teratogenicity in humans is lacking, and even those believing the drug is teratogenic agree that the rates are quite small. While counseling pregnant women on their teratogenic risk, it was our impression that there is an unrealistically high perception of reproductive risk of cocaine. We wished to quantify the perception of teratogenic risk of cocaine by the public, physicians, and by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It has been shown that the tendency to terminate pregnancy significantly decreased after an antenatal consultation about drug exposition. 11,12 Moreover, counselling can decrease the perception of teratogenic risk by women themselves. 13 Another point concerns the way the risk is communicated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the tendency to terminate pregnancy significantly decreased after an antenatal consultation about drug exposition. 11,12 Moreover, counselling can decrease the perception of teratogenic risk by women themselves. 13 Another point concerns the way the risk is communicated.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature finds support for cocaine teratogenicity in the majority of reports [1][2][3][4][5], but not all [6][7][8], Animal studies clearly support the teratogenic po tential of cocaine [9,[13][14][15][16]20] by a vascular disruption mechanism. Chasnoff et al [1] reported an increased inci dence of genital tract malformations in neonates exposed to prenatal cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies support co caine teratogenicity [1][2][3][4][5] this association [6][7][8]. The pathogenic mechanism and unique pharmacokinetics of cocaine in pregnancy make it a likely candidate teratogen [9], Vascular accidents occur in adult users of cocaine [10][11][12], In addition, cocaine adversely alters maternal-fetal hemodynamics [13,14], However, the occurrence of a congenital anomaly require the specific time-dependent action of the drug in a suscep tible tissue, and the recognition of both the anomaly and the prenatal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…8 It is also currently being used for myeloma, and thalidomide-like agents have become standard of care for multiple myeloma treatment. However, the suffering it caused has prompted the common belief that every drug has the potential to be a new thalidomide, 9 and patients commonly discontinue treatment and often unnecessarily consider an abortion of a wanted pregnancy. 10 There are only a limited number of drugs proven to be human teratogens, including thalidomide, isotretinoin, coumarin derivates, valproic acid, and folate antagonists.…”
Section: The Scope Of the Issuementioning
confidence: 99%